Melatonin mitigates root growth inhibition and carbon-nitrogen metabolism imbalance in apple rootstock M9T337 under high nitrogen stress - Sun, Maoxiang; Wang, Chaoran; Zhang, Guowei; Cao, Hui; Wang, Fen; Li, Ming; Ge, Shunfeng (Frontiers in Plant Science, 2024)
Nitrogen (N) is an essential element for plant growth, development, and metabolism.In apple production, the excessive use of N fertilizer may cause high N stress. Whether high N stress can be alleviated by regulating melatonin supply is unclear. The effects of melatonin on root morphology, antioxidant enzyme activity and 13 C and 15 N accumulation in apple rootstock M9T337 treated with high N were studied by soil culture. The results showed that correctly raising the melatonin supply level is helpful to root development of M9T337 rootstock under severe N stress. Compared with HN treatment, HN+MT treatment increased root growth, stem growth, and leaf growth by 11.38%, 5.44%, and 28.01%, respectively. Under high N conditions, appropriately increasing melatonin level can activate antioxidant enzyme activity, reduce lipid peroxidation in roots, protect root structural integrity, promote the transport of sorbitol and sucrose to roots, and promote further degradation and utilization of sorbitol and sucrose in roots, which is conducive to the accumulation of photosynthetic products, thereby reducing the inhibitory effect of high N treatment on root growth. Under high N stress, melatonin significantly promotes nitrate absorption, enhances N metabolism enzyme activity, and upregulates related gene expression, and regulate N uptake and utilization in the M9T337 rootstock. These results presented a fresh notion for improving N application and preserving carbon-nitrogen balance.